If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 6c + -2 = 12 Reorder the terms: -2 + 6c + 5x = 12 Solving -2 + 6c + 5x = 12 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 6c + 2 + 5x = 12 + 2 Reorder the terms: -2 + 2 + 6c + 5x = 12 + 2 Combine like terms: -2 + 2 = 0 0 + 6c + 5x = 12 + 2 6c + 5x = 12 + 2 Combine like terms: 12 + 2 = 14 6c + 5x = 14 Add '-5x' to each side of the equation. 6c + 5x + -5x = 14 + -5x Combine like terms: 5x + -5x = 0 6c + 0 = 14 + -5x 6c = 14 + -5x Divide each side by '6'. c = 2.333333333 + -0.8333333333x Simplifying c = 2.333333333 + -0.8333333333x
| 3(6z-1)-3(z+7)=8(z+1) | | 15m=16 | | -(4y+1)-(-3y-7)=0 | | 4x*x-13x+7=0 | | 4x^2-7x-8=0 | | 2x+5x^2=12 | | -2-2x=1 | | 0=9x^2+6x-3 | | 21x=-147 | | -2-2x=-1 | | -2-2x=-2 | | 4x*-13x+7=0 | | -2-2x=2 | | 32=-16^2+64t+4 | | 4n+6=35 | | 9x0188 | | 25w^2+90wg+81g^2=0 | | 25w^2+90wg+81g^2 | | 4xx-13x+7 | | 16(3x-8)=4(12x+9) | | 7+10s-2=8s+13-2s | | c^2=-1 | | x^3+6x^2+11x+36=0 | | 50-110=40 | | x^4+3x^3+2x^2+5x-7=0 | | 4t=-36 | | -2(3b+4)+(7b-4)=0 | | [2(x-2)-5]+[7(x+1)+7]= | | 1.4q-2.2-3.2q=2.8-4.7 | | 16-7i=58 | | x-11=26 | | 16-4w=24 |